People's Republic of China : Hong Kong Special Administrative Region -- Report on the Observance of Standards and Codes. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses key findings of the Report on the Observance of Standards and Codes for Hong Kong Special Administrative Region (HKSAR). HKSAR has a very high level of compliance with the Basel Core Principles for Effective Banking Supervision. The Hong Kong Monetary Authority (HKMA) complements its high supervisory standards with a sustained commitment to the international regulatory reform agenda where it is an early adopter of many standards. The banking system is characterized by the dominant presence of institutions with foreign ownership, including the systemic banks, which puts a premium on the HKMA's role as a host supervisory authority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet